Electromagnetic and mechanical properties of Fe3O4-coated amorphous carbon nanotube/polyvinyl chloride composites. Issue 9 (21st November 2016) - Hou, Cuiling; Song, Shihua; Zhou, Xueyun; Wei, Jianning; Li, Tiehu
Abstract: Electromagnetic wave absorbing properties of absorbing composites depend on the dielectric and magnetic loss generally. In this paper, using Fe3 O4 -coated amorphous carbon nanotubes (ACNTs-Fe3 O4 ) fabricated using a chemical synthesis–hydrothermal treatment method as an absorber and polyvinyl chloride (PVC) as a matrix, electromagnetic and mechanical properties of ACNT-Fe3 O4 /PVC composite were investigated. The results showed that the dielectric and magnetic losses of ACNT-Fe3 O4 /PVC composite were significantly enhanced in 8.2–12.4 GHz compared to ACNT/PVC composite, which improved absorbing properties, while slightly changing the mechanical properties.